Bioaccumulation of selected metals in fresh water haruan fish (channa striatus) collected from Pahang River Basin, Malaysia - Khan Chowdhury, Ahmed Jalal; John, Akbar; Habab, M.; Mohd, A.Y.; Yunus, Kamaruzzaman (Oriental Scientific Publishing Co., 2013)
A study on Copper (Cu), Zinc (Zn) and Lead(Pb) concentration in fresh water fish Channastriatus -Haruan fish in Pahang, Malaysia was conducted. Three types of fish organs were studied. The organs were; liver, muscle and intestine. They were dissected and dried before the digestion process using HNO3, H2SO4, H2O2 and HCL. Inductively Coupled Plasma Spectrometry (ICP-MS) was used for the detection of heavy metals. There was a significant variation in the concentration of zinc was observed between tissues of the studied fish (P< 0.05) while copper and lead showed no significant difference in accumulation between selected tissues. Nevertheless, the findings from this study revealed that all the heavy metals concentrations in the tissues were lower than the maximum permissible limit as recommended by The Malaysian Food Regulation and hence safe for human consumption. Long term monitoring study is needed to implement various fishery management plans to safeguard the quality of C. striatus wild stock.